New production methods for salient pole rotor manufacture - Sumner, Aaran (2018)
The current design for a salient pole rotor consists of hundreds of laminations joined together to form a core pack, which is then pressed onto shaft. This thesis examines the possibility of using a solid cast rotor to reduce the complexity of rotor construction. To produce a solid salient pole rotor that has the capability to match the performance of the current lamination based rotor three fundamental areas which affect rotor performance were investigated. They are: • The magnetic performance of cast steel and a lower saturation Fe-Ni alloy for the magnetic shielding of pole faces. • The comparison of the performance of a solid steel rotor verses the lamination based rotor. • The use of laser cladding to produce a soft magnetic coating to prevent eddy currents from being induced into the rotor. Samples of cast steel were tested after various heat treatments were applied and their DC B-H curves were measured. The samples were examined, via optical microscopy, to determine the effect of heat treatments on their microstructure. The changes in their B-H curves and permeability were linked to the changes in microstructure by examination of the optical images. A prototype of a solid rotor was produced to determine its performance compared with the lamination based rotor. The prototype rotor was produced with a Fe-Ni alloy on the rotor pole faces. The prototype rotor was found to require an average of 72% more power in the field windings to match the performance of the lamination based rotor. This was true until the generator’s output reached 72kW when the Fe-Ni alloy on the rotor pole faces saturated, resulting in the air gap between the rotor and stator increasing from 2mm to 34.5mm. After the increase in air gap the prototype rotor required an average of 188% more power to match the lamination based rotor. The point at which the Fe-Ni alloy saturates is critical, as once saturated the power in the field windings must increase sharply to bridge the larger air gap. From this work it is clear that a cast steel with a better magnetic performance is required and that the point at which the lower saturation material on the pole shoes saturates needs to more closely match the normal operating power of the generator. Laser cladding was used to produce a coating that can be applied to the pole faces, with a sufficient thickness to allow a controllable increase in the air gap between the rotor and the stator at predetermined field strengths. The use of laser cladding in this way enables the pole face to act as a magnetic shield stopping heating in the rotor due to induced eddy currents. The use of annealing in both inert and reactive atmospheres was examined to determine their effect on the DC magnetic properties of the deposited coating. Annealing in an inert atmosphere of argon was found to improve the saturation magnetisation of the coating 30% better than annealing in a reactive hydrogen atmosphere.